The association between parental support and monitoring and substance use among adolescence; ADHD symptoms and delinquent peer influences as risk factors - Karítas Líf Óskarsdóttir 2000- (2023)
Parental support and monitoring are protective factors against substance use. However, low parental monitoring and support are linked with adolescents involving themselves with delinquent peers, increasing the risk of substance use. Also, symptoms of ADHD are found to be a significant risk factor for adolescent substance use. Therefore, this study aimed to examine the relationship between parental support and monitoring of substance use among adolescents and investigate if ADHD symptoms and delinquent peer influences reduce the protective effect of parental support and monitoring. Participants in this study were elementary students in the 8th to 10th grade (N= 2000) who participated in the Youth in Iceland survey in 2014. The findings suggest that parental support and monitoring, delinquent peer influences, and higher levels of ADHD symptoms all had significant relationships with substance use among adolescents. Also, a moderation and mediation analysis was conducted, and the results showed a partial mediation relationship between parental support and monitoring and substance use with delinquent peer influences as mediators. Still, ADHD was not found to have a moderating effect on the association. These findings indicate that parental support and monitoring are protective factors for adolescents’ substance use, and ADHD and delinquent peer influences are risk factors for adolescents’ substance use. Keywords: substance use, parental support and monitoring, ADHD, delinquent peer influences Stuðningur og eftirlit foreldra er talinn vera verndandi þáttur gegn notkun á vímuefnum. Skortur af eftirliti og stuðningi foreldra getur leitt til þess að ungmenni leita í slæman vinskap sem eykur hættuna á að leiðast út í vímuefnanotkun. ADHD er einnig talinn vera áhættuþáttur í sambandi við notkun vímuefna hjá ungmennum. Tilgangur rannsóknarinnar var að kanna frekar sambandið milli stuðning og eftirlit foreldra á vímuefnanotkun ungmenna og kanna hvort að ADHD og slæm vinasambönd dragi úr verndandi áhrifum af stuðningi og ...